FIXED MONITORING SYSTEM FOR MONITORING GAS GENERATED IN WASTE LANDFILL - Wahjono, Heru Dwi (BPPT)
Gas produced by landfill is bio-gas that has a high concentration of methane that could cause global warming if not controlled. Good management of a landfill in controling the production of methane gas, can be used as an alternative sources of energy to produce electrical energy. Monitoring of methane gas production needs to be done continuously for the energy conversion process can take place perfectly without polluting the environment. Fixed monitoring system described in this paper is the result of design and development including hardware and software of monitoring technology for methane gas to facilitate research in doing observations of a landfill performance.keywords : final disposal, landfill gas, methane, landfill performance, fixed landfill gas monitoring system